The necessity of voiding cystourethrogram for the evaluation of recipient candidates in adult renal transplantation - M. Sarier; M. Callioglu; Yu. Yuksel (Вестник трансплантологии и искусственных органов, 2020)
Objective. While international guidelines necessitate Voiding Cystourethrogram (VCUG) for pediatric patients, it is unnecessary for the evaluation of adult patients without urological disorders as renal transplant candidates. The objective of this study was to evaluate the results of adult candidates who underwent VCUG before transplantation and to demonstrate the necessity for this imaging. Methods. A retrospective study of the data of 1265 adult candidates who underwent VCUG before transplantation at our center, was undertaken. VUR, the presence of Postvoiding residual urine (PVR) (>100 ml), Low bladder capacity (LBC) (<100 ml), and urethral pathologies were evaluated with VCUG. Results. The mean age was 42.3 ± 1.3. The mean dialysis period was 27.8 ± 4.2 months. According to the VCUG results, 19.2% of the patients had pathological findings. On the other hand, the rate of urological disorders was only 5.1%, according to end-stage renal disease (ESRD) etiologies. VCUG outcomes indicated bilateral high-grade reflux in native kidneys in 4.4% (n = 56) of the candidates, unilateral high-grade reflux in 4.1% (n = 52), bilateral low grade reflux in 2.1% (n = 26), unilateral low-grade reflux in 2.4% (n = 30), and reflux in rejected transplanted kidney in 2.3% (n = 29). In addition, significant LBC was noted in 4.8% (n = 61), significant PVR in 1.1% (n = 14), and urethral stricture in 0.5% (n = 6) of the candidates. Conclusion. VCUG should be considered as a part of routine evaluation in adult renal transplant recipient candidates as well as in pediatric candidates, even if their ESRD etiologies are not due to urological disorders.